From 'no further action' to taking action: England's shifting social work responses to extra-familial harm. (1st March 2022) - Firmin, Carlene; Lloyd, Jenny; Walker, Joanne; Owens, Rachael
Abstract : In 2018, England's safeguarding guidelines were amended to explicitly recognise a need for child protection responses to extra-familial harms. This article explores the feasibility of these amendments, using quantitative and qualitative analysis of case-file data, as well as reflective workshops, from five children's social care services in England and Wales, in the context of wider policy and practice frameworks that guide the delivery of child protection systems and responses to harm beyond families. Green shoots of contextual social work practice were evident in the data set. However, variance within and across participating services raises questions about whether contextual social work responses to extra-familial harm are sustainable in child protection systems dominated by a focus on parental responsibility. Opportunities to use contextual responses to extra-familial harm as a gateway to reform individualised child protection practices more broadly are also discussed.